Pengaruh Self-Efficacy, Adversity Quotient, dan Entrepreneurial Alertness terhadap Intensi Berwirausaha - Ramadhani, Santi Fauziah; Marna, Jean Elikal (Jurnal Ecogen, 2024)
This research was conducted to determine the influence of Self-Efficacy, Adversity Quotient, and Entrepreneurial Alertness on the Entrepreneurial Intentions of Students at the Faculty of Economics and Business, Universitas Negeri Padang. The type of data used in this research is quantitative. The population used in this research was 1089 undergraduate students who had passed the mandatory entrepreneurship and entrepreneurial practice courses. The sampling technique used in this research was proportional random sampling with a sample size of 92. The data collection technique in this research used a questionnaire via Google Form with a Likert scale. The analysis method in this research is multiple linear regression with the SPSS V.20 application. To test the hypothesis in this study, we used validity and reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, determination tests, F tests, and T tests. The results of this research show that 1) Self-Efficacy has a positive and significant effect on students' entrepreneurial intentions 2 ) Adversity Quotient has no effect on students' entrepreneurial intentions 3) Entrepreneurial Alertness has no effect on students' entrepreneurial intentions 4) Self-Efficacy, Adversity Quotient, and Entrepreneurial Alertness together have a positive and significant effect on students' entrepreneurial intentions.